Extraction of selected prohealth substances from Curcuma longa and Zingiber officinale in artificial digestive juices - Krakowska, Agata; Kała, Katarzyna; Rospond, Bartłomiej; Szewczyk, Agnieszka; Opoka, Włodzimierz; Muszyńska, Bożena (Journal of the science of food and agriculture, 2022)
BACKGROUND The study determined the content of selected bioelements, toxic metals and phenolic acids occurring in Curcuma longa L. and Zingiber officinale Rosc. Natural raw materials in the form of powder, slices, dried and fresh rootstock, tablets and capsules were analyzed. To determine the actual bioavailability of the metals and phenolic acids present in the raw materials, they were extracted into artificial digestive juices (artificial gastric and intestinal juices). RESULTS The maximum amounts of bioelements found in turmeric were as follows (mg kg−1 dry weight): Ca, 1911; Cu, 10.4; Fe, 248; K, 123; Mg, 1896; Mn, 181; Na, 332; Zn, 242. On the other hand, the maximum amounts of these bioelements found in ginger were as follows (mg kg−1 dry weight): Ca, 287; Cu, 7.4; Fe, 113; K, 2903; Mg, 1162; Mn, 11.3; Na, 1678; Zn, 186. It was found that bioelements from all the tested samples of raw materials were released to artificial digestive juices. CONCLUSION The amount of substances extracted to digestive juices from the analyzed raw materials varied depending on their form. The highest content of bioelements was found in the fresh rhizomes of turmeric and ginger. On the other hand, powdered rhizome was characterized by the highest bioavailability of elements for humans. © 2021 Society of Chemical Industry